BETWEEN RISK TOLERANCE AND FINANCIAL RESILIENCE: A STUDY ON INDUSTRIAL WORKERS IN BATAM CITY - Etty Sri Wahyuni; Henry Aspan; Ari Prabowo (RADJA PUBLIKA, 2025)
Abstract This study examines the mediating role of retirement planning in the relationship between risk tolerance and financial resilience among industrial workers in Batam City, Indonesia. Using a quantitative cross-sectional survey design, data were collected from 78 permanent industrial workers employed in manufacturing companies across Batam's industrial zones through purposive sampling. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses regarding direct relationships and mediation effects. The measurement model demonstrated satisfactory reliability and validity, with Cronbach's Alpha values ranging from 0.892 to 0.968 and Average Variance Extracted (AVE) meeting acceptable thresholds. The structural model analysis revealed significant positive relationships across all hypothesized paths. Risk tolerance showed the strongest relationship with retirement planning (β = 0.640, t = 9.317, p < 0.001), while retirement planning demonstrated substantial positive effects on financial resilience (β = 0.609, t = 5.202, p < 0.001). Risk tolerance also exhibited a direct positive relationship with financial resilience (β = 0.339, t = 2.555, p = 0.011). Most importantly, the mediation analysis confirmed that retirement planning partially mediates the relationship between risk tolerance and financial resilience, with a significant indirect effect (β = 0.390, t = 3.898, p < 0.001) that exceeds the direct effect. The findings contribute to behavioral finance literature by demonstrating that retirement planning serves as a critical mechanism through which individual risk preferences translate into financial resilience outcomes among industrial workers in emerging market contexts. The results support lifecycle theory and planned behavior theory, showing that systematic retirement planning behaviors are more effective than spontaneous risk-taking activities in enhancing financial resilience. Practical implications suggest that financial literacy programs should focus on retirement planning education tailored to workers' risk tolerance levels, while policymakers can develop targeted interventions leveraging individual risk preferences to improve workers' long-term financial well-being. The study provides valuable insights for enhancing financial resilience among Indonesia's industrial workforce in the context of evolving social security systems and demographic transitions.